Strategi Peningkatan Loyalitas Mahasiswa Perguruan Tinggi IIB Darmajaya Bandar Lampung - Saputra, Muhammad; Putri, Anandha Sartika (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The research objective is to analyze what factors influence student loyalty as internal consumers in promoting IIB Darmajaya College in Bandar Lampung. This associative-causality study used 100 samples selected by purposive sampling. Methods of data analysis using multiple linear regression analysis. The results obtained that partially, service quality, satisfaction and trust were identified as having no effect on student loyalty; but the brand image of the institution has proven to have an effect on the loyalty of the college students concerned. Simultaneous test results show that service quality, satisfaction, trust and brand image have a significant effect on student loyalty at IIB Darmajaya Bandar Lampung college students. It is recommended that the campus develop and strengthen a branding strategy so that it can encourage student loyalty in recommending IIB Darmajaya education to potential consumers.